MANAGEMENT ACCOUNTING IN DESIGNING PERFORMANCE EVALUATION AND CONTROL SYSTEMS IN THE HYBRID WORK ERA: IMPLICATIONS FOR PSYCHOLOGICAL SAFETY AND PERCEIVED FAIRNESS - Henny Rakhmawati; Bondan Subagyo (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study explores the role of Adaptive Management Control Systems (AMCS) in enhancing employee performance within hybrid work environments, emphasizing the behavioral factors of perceived fairness and psychological safety. As organizations adapt to remote and hybrid models, management accounting practices must evolve to maintain performance and engagement. This research aims to examine the direct impact of AMCS on performance, the mediating role of fairness perception, and the moderating effect of psychological safety. A quantitative method was employed using a survey of 75 employees working under hybrid arrangements in Indonesia. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that AMCS significantly improves employee performance, both directly and indirectly through perceived fairness. Additionally, psychological safety strengthens the relationship between AMCS and performance. These findings suggest that effective management control in hybrid settings requires attention not only to structure but also to employees’ behavioral and psychological experiences. This study contributes to the development of behaviorally-informed management control systems and offers practical insights for organizations aiming to optimize performance in flexible work environments.